(untitled) (Heritage, 2022)
In this paper the author presents results of research on the position of Serbs in Kosovska Mitrovica in the context of the integration of the north of Kosovo and Metohija into the institutional system of the self-proclaimed independent Kosovo, foreseen by the Brussels Agreement from 2013. The focus of the paper is on the attitude of the Serbs in Kosovska Mitrovica towards the outcomes of the Brussels Agreement, where the emphasis is placed on viewing the way in which the members of the researched Serbian community talk about their position from the aspect of one of the main sentiments woven into their experience of their own status practically all the time since the ethnic division of Kosovska Mitrovica in 1999 until today, and that is the feeling of apprehention from an uncertain tomorrow. In a situation where they are practically excluded from making decicions regarding the application of the Brussels agreement, the research was motivated by the effort to enable the Serbs in Kosovska Mitrovica to “speak”, in the hope that their voice will reach not only the scientific, but also the wider social public. The goal of the paper, in that sense, is aimed at understanding the way in which the Serbs in Kosovska Mitrovica describe their current situation, that is, at providing an answer to the question of how, in the context of feeling uncertainty about tomorrow, they think about their future. The method applied in achieving the set goal was based on the emic, anthropological key perspective, which means that the author used the qualitative research approach, primarily the conversation with interlocutors. The results presented in the paper were obtained on the basis of field research conducted in Kosovska Mitrovica on several occations during 2022.